Multidimensional context of technical nursing education: triangulation of meanings attributed by teachers* - Sousa, Bruna Sabrina de Almeida; Nunes, Benevina Maria Vilar Teixeira; Porto, Fernando Rocha; Nery, Inez Sampaio; Moura, Maria Eliete Batista; Carvalho, Herica Emilia Félix de (Revista da Escola de Enfermagem da USP, 2022)
Objective: To unveil and discuss the meanings attributed by teachers to the teacher-student relationship in the multidimensional context of technical nursing education. Method: Qualitative research, supported by the representational theory of meaning, carried out with nine nurses who teach the technical nursing course at a technical school linked to a federal university in the northeastern region of Brazil. Results: The following meanings were revealed: student profile; lack of preparation and financial resources; reduction in performance and even course interruption; students’ disinterest and resistance; academic support and qualified structure; opportunity for grants; teachers’ dedication and holistic view; respect, ethics, and interactivity; concern with student learning and performance, and heterogeneous group. Conclusion: Social and financial difficulties and students’ disinterest are the limitations that most hinder teaching effectiveness. On the other hand, the teachers’ holistic view, dedication, support, and the availability of resources and academic support are the main multidimensional characteristics of living in this scenario.